Organosolv pretreatment assisted by carbocation scavenger to mitigate surface barrier effect of lignin for improving biomass saccharification and utilization - Qiulu Chu; Wenyao Tong; Jianqiang Chen; Shufang Wu; Yongcan Jin; Jinguang Hu; Kai Song (Biotechnology for Biofuels, 2021)
Abstract Background Ethanol organosolv (EOS) pretreatment is one of the most efficient methods for boosting biomass saccharification as it can achieve an efficient fractionation of three major constituents in lignocellulose. However, lignin repolymerization often occurs in acid EOS pretreatment, which impairs subsequent enzymatic hydrolysis. This study investigated acid EOS pretreatment assisted by carbocation scavenger (2-naphthol, 2-naphthol-7-sulfonate, mannitol and syringic acid) to improve biomass fractionation, coproduction of fermentable sugars and lignin adsorbents. In addition, surface barrier effect of lignin on cellulose hydrolysis was isolated from unproductive binding effect of lignin, and the analyses of surface chemistry, surface morphology and surface area were carried out to reveal the lignin inhibition mitigating effect of various additives. Results Four different additives all helped mitigate lignin inhibition on cellulose hydrolysis in particular diminishing surface barrier effect, among which 2-naphthol-7-sulfonate showed the best performance in improving pretreatment efficacy, while mannitol and syringic acid could serve as novel green additives. Through the addition of 2-naphthol-7-sulfonate, selective lignin removal was increased up to 76%, while cellulose hydrolysis yield was improved by 85%. As a result, 35.78 kg cellulose and 16.63 kg hemicellulose from 100 kg poplar could be released and recovered as fermentable sugars, corresponding to a sugar yield of 78%. Moreover, 22.56 kg ethanol organosolv lignin and 17.53 kg enzymatic hydrolysis residue could be recovered as lignin adsorbents for textile dye removal, with the adsorption capacities of 45.87 and 103.09 mg g−1, respectively. Conclusions Results in this work indicated proper additives could give rise to the form of less repolymerized surface lignin, which would decrease the unproductive binding of cellulase enzymes to surface lignin. Besides, the supplementation of additives (NS, MT and SA) resulted in a simultaneously increased surface area and decreased lignin coverage. All these factors contributed to the diminished surface barrier effect of lignin, thereby improving the ease of enzymatic hydrolysis of cellulose. The biorefinery process based on acidic EOS pretreatment assisted by carbocation scavenger was proved to enable the coproduction of fermentable sugars and lignin adsorbents, allowing the holistic utilization of lignocellulosic biomass for a sustainable biorefinery. Graphic abstract